Prostate Cancer Predicting Factors: A Preliminary Report from Tehran - Pourmand, Gholamreza; Allameh, Farzad; Mohammad, Kazem; Dehghani, Sanaz; Pourmand, Bita; Mehrsai, Abdolrasoul; Hosseini, Seyed Hamed (Urology Journal, 2012)
PURPOSE: To determine the probability of having prostate cancer (PCa) using the combination of serum level of prostate-specific antigen (PSA) and age. MATERIALS AND METHODS: A total of 160 patients and 190 controls were enrolled in this hospital-based case-control study. Using a logistic regression model and the odds ratio of age and PSA level, the probability of PCa was estimated based on serum level of PSA and age of the participants. RESULTS: The mean age of patients with PCa and benign prostatic hyperplasia (BPH) was 67.75 ± 8.81 and 62.07 ± 8.71 years, respectively (P < .000). Using univariate analysis, we found that increase in life decades of the cases almost doubles the risk of having PCa (odds ratio = 1.95; P = .00), and the probability of developing cancer may increase by 74% in ketchup consumers. After multiple variable regressions, it was revealed that the odds of developing PCa increase by 90% only for every decade, and other variables did not have any significant association with PCa. CONCLUSION: In clinical practice, PSA level combined with the age at presentation can be used as predictors of PCa probability and the necessity of biopsy.